The development of mechanically formed stable nanobubbles intended for sonoporation-mediated gene transfection - Rodi Abdalkader; Shigeru Kawakami; Johan Unga; Yuriko Higuchi; Ryo Suzuki; Kazuo Maruyama; Fumiyoshi Yamashita; Mitsuru Hashida (Taylor & Francis Group, 2017)
In this study, stable nano-sized bubbles (nanobubbles [NBs]) were produced using the mechanical agitation method in the presence of perfluorocarbon gases. NBs made with perfluoropropane had a smaller size (around 400 nm) compared to that of those made with perfluorobutane or nitrogen gas. The lipid concentration in NBs affected both their initial size and post-formulation stability. NBs formed with a final lipid concentration of 0.5 mg/ml tended to be more stable, having a uniform size distribution for 24 h at room temperature and 50 h at 4 °C. In vitro gene expression revealed that NBs/pDNA in combination with ultrasound (US) irradiation had significantly higher transfection efficacy in colon C26 cells. Moreover, for in vivo gene transfection in mice left limb muscles, there was notable local transfection activity by NBs/pDNA when combined with US irradiation. In addition, the aged NBs kept at room temperature or 4 °C were still functional at enhancing gene transfection in mice. We succeeded in preparing stable NBs for efficient in vivo gene transfection, using the mechanical agitation method.